An efficient error compensation method for coordinated CNC five-axis machine tools. (December 2017) - Zhao, Dan; Bi, Yunbo; Ke, Yinglin
Abstract: The paper introduces a new automatic drilling and riveting system for aircraft assembly which is composed of two five-axis machine tools in coordination. As a dual-machine system, relative position and orientation accuracy of coordinated machines is the decisive factor for high fastening quality. Considering all static/quasi-static error sources deteriorating relative positioning accuracy, an effective error compensation method which consists of a new error prediction model and an error compensation strategy is proposed for coordinated five-axis machines. Based on the decomposition concept, the coordinated workspace of dual machines is described as the superposition of the coordinated workspace of prismatic joints (CWP) and the coordinated workspace of revolute joints (CWR). They are separated to study the influence on the objective error, and a combined interpolation algorithm based on the shape functions is proposed for error prediction, which can avoid the curse of dimensionality essentially and be efficient to predict the relative position and orientation errors at any desired pose in the coordinated workspace of dual machines. For the error compensation of dual-machine system, a basic strategy is proposed which is to take the position and orientation of the driving machine as the reference and compensate the predicted error for the driven machine through the motion commands modification. To verify the feasibility of proposed method, experiments have been performed on the developed dual-machine system with different error compensation methods. The results show that the proposed method is more efficient which needs less time for sampled data measurement and calculation, and the relative positioning accuracy of the compensated dual-machine system is improved to 0.072 mm and 0.017° which meet the requirements for automatic drilling and riveting in aircraft assembly. Highlights: A new automatic drilling and riveting system is developed for aircraft assembly. An efficient error compensation method for the dual-machine system is proposed. An error prediction model based on mesh and decomposition concepts is established. A compensation strategy is proposed to reduce relative pose error of dual machines. The positioning accuracy of compensated dual-machine system is greatly improved.